2017
DOI: 10.1534/genetics.117.201491
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hyphal Growth and N-Acetylglucosamine Catabolism by Two Transcription Factors in Candida albicans

Abstract: The amino sugar N-acetylglucosamine (GlcNAc) is increasingly recognized as an important signaling molecule in addition to its well-known structural roles at the cell surface. In the human fungal pathogen Candida albicans, GlcNAc stimulates several responses including the induction of the genes needed for its catabolism and a switch from budding to filamentous hyphal growth. We identified two genes needed for growth on GlcNAc (RON1 and NGS1) and found that mutants lacking these genes fail to induce the genes ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 64 publications
1
28
4
Order By: Relevance
“…Engineered carbon-deficient mutants are impaired in multiple virulence models. As a second and more direct approach to address this issue, we employed the CRISPR-Cas9 system to generate strains lacking one or more of the genes that have been previously shown to directly contribute to nutrient import and catabolism, i.e., STP2, JEN1, JEN2, HXK1, NAG1, and DAC1 (11,29,32). Stp2 is a transcription factor that controls amino acid import and catabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineered carbon-deficient mutants are impaired in multiple virulence models. As a second and more direct approach to address this issue, we employed the CRISPR-Cas9 system to generate strains lacking one or more of the genes that have been previously shown to directly contribute to nutrient import and catabolism, i.e., STP2, JEN1, JEN2, HXK1, NAG1, and DAC1 (11,29,32). Stp2 is a transcription factor that controls amino acid import and catabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma membrane SPS amino acid sensor (Ssy1, Ptr3, Ssy5) regulates Stp2 and has very similar macrophage phenotypes (67), but it is not clear whether sensing and metabolism can be decoupled. GlcNac sensing (by Ngs1) and import (through Ngt1) are required for hyphal induction (29), suggesting that catabolism may also be dispensable for GlcNAc-induced stress resistance. Separating nutrient sensing and catabolism for pathogenesis and stress resistance will provide new insights into how pathogenic fungi detect, interact with, and adapt to various host environments.…”
Section: Discussionmentioning
confidence: 99%
“…Two orthologs with 20-26% of homology have been identified in the A. fumigatus genome. Yet, no protein homology was observed between Cda7 and the GlcNAc sensors such as Ngs1, the GlcNAc deacetylase Nag2 which is part of the NAG regulon governing the GlcNAc signalization pathway in C. albicans, nor Gig1 (Su et al, 2016;Naseem et al, 2017). The production of recombinant Cda proteins of A. fumigatus, as well as the analysis of the expression of the different CDA's in presence of GlcNAc or GlcN will be required to elucidate the role of CDAs in A. fumigatus.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of GlcNAc in hyphal induction is through a mechanism sensitive to inhibitors of cAMP-dependent protein kinase in C. albicans (Castilla et al, 1998), whereas only a normal basal level of cAMP, but not a pulse of cAMP-PKA activation, is needed (Parrino et al, 2017). Recent study reported that the GlcNAc-sensor and transducer Ngs1 is important for GlcNAc-induced hyphal development, especially hyphal transcription in log phase cells (Su et al, 2016;Naseem et al, 2017). The N-terminal b-N-acetylglucosaminidase homology domain in Ngs1 can bind GlcNAc, and this binding activates its C-terminal GCN5-related N-acetyltransferase (GNAT) domain.…”
Section: Introductionmentioning
confidence: 99%